PEMANFAATAN HUTAN ADAT OLEH MASYARAKAT SUKU SOUG DI KABUPATEN MANOKWARI SELATAN - DECKY REINGGUP; ANTON SILAS SINERY; CHARLY BRAVO WANGGAI (JURNAL KEHUTANAN PAPUASIA, 2020)
The purpose of this study was to identify the customary community forest of Soug tribe of Arfak in using customary forest resources surrounding Tobou forest. Through the study, how the forest assessed, local culture, forest preservation, transfer knowledge, accessibility, and infrastructure towards the existence of Tobou customary forest. The descriptive method was used to qualitative data. In order to obtain data, interview, and field observation was applied. In terms of customary forest use around Tobou, there were numbers of conserving land types such as garden opening, extracting both, timber and non-timber forest products, important value and trust, co-benefit interaction among social and biophysical co-benefit as a whole ecosystem component and customary role community. It turned out that social bonds among community strata were glaringly seen through customary roles as it has been indicated strongly in Arfak ethnic.